New insights into the biological roles of immune cells in neural stem cells in post-traumatic injury of the central nervous system - Ning He; Xing-Jia Mao; Yue-Min Ding; Tong Zuo; Ying-Ying Chen; Lin-Lin Wang (Neural Regeneration Research, 2023)
Traumatic injuries in the central nervous system, such as traumatic brain injury and spinal cord injury, are associated with tissue inflammation and the infiltration of immune cells, which simultaneously affect the self-renewal and differentiation of neural stem cells. However, the tissue repair process instigated by endogenous neural stem cells is incapable of restoring central nervous system injuries without external intervention. Recently, resident/peripheral immune cells have been demonstrated to exert significant effects on neural stem cells. Thus, the restoration of traumatic injuries in the central nervous system by the immune intervention in neural stem cells represents a potential therapeutic method. In this review, we discuss the roles and possible mechanisms of immune cells on the self-renewal and differentiation of neural stem cells along with the prognosis of central nervous system injuries based on immune intervention. Finally, we discuss remaining research challenges that need to be considered in the future. Further elucidation of these challenges will facilitate the successful application of neural stem cells in central nervous system injuries.